Small airway function in Finnish COVID-19 survivors - Lindahl Anna; Reijula Jere; Malmberg Leo Pekka; Aro Miia; Vasankari Tuula; Mäkelä Mika Juhani (BMC, 2022)
Follow-up studies of COVID-19 patients have found lung function impairment up to six months after initial infection, but small airway function has not previously been studied. Patients (n = 20) hospitalised for a severe SARS-CoV-2 infection underwent spirometry, impulse oscillometry, and multiple measurements of alveolar nitric oxide three to six months after acute infection. None of the patients had small airway obstruction, nor increased nitric oxide concentration in the alveolar level. None of the patients had a reduced FEV1/FVC or significant bronchodilator responses in IOS or spirometry. In conclusion, we found no evidence of inflammation or dysfunction in the small airways.